Apoptosis and Autophagy: Current Understanding in Tick–Pathogen Interactions - Wang, Xin-Ru; Cull, Benjamin (Frontiers in Cellular and Infection Microbiology, 2022)
Tick-borne diseases are a significant threat to human and animal health throughout the world. How tick-borne pathogens successfully infect and disseminate in both their vertebrate and invertebrate hosts is only partially understood. Pathogens have evolved several mechanisms to combat host defense systems, and to avoid and modulate host immunity during infection, therefore benefitting their survival and replication. In the host, pathogens trigger responses from innate and adaptive immune systems that recognize and eliminate invaders. Two important innate defenses against pathogens are the programmed cell death pathways of apoptosis and autophagy. This Mini Review surveys the current knowledge of apoptosis and autophagy pathways in tick-pathogen interactions, as well as the strategies evolved by pathogens for their benefit. We then assess the limitations to studying both pathways and discuss their participation in the network of the tick immune system, before highlighting future perspectives in this field. The knowledge gained would significantly enhance our understanding of the defense responses in vector ticks that regulate pathogen infection and burden, and form the foundation for future research to identify novel approaches to the control of tick-borne diseases.